Use of Isotope Effects To Understand the Present and Past of the Atmosphere and Climate and Track the Origin of Life. (14th February 2019) - Thiemens, Mark H.; Lin, Mang
Abstract: Stable isotope ratio measurements have been used as a measure of a wide variety of processes, including solar system evolution, geological formational temperatures, tracking of atmospheric gas and aerosol chemical transformation, and is the only means by which past global temperatures may be determined over long time scales. Conventionally, isotope effects derive from differences of isotopically substituted molecules in isotope vibrational energy, bond strength, velocity, gravity, and evaporation/condensation. The variations in isotope ratio, such as 18 O/ 16 O (δ 18 O) and 17 O/ 16 O (δ 17 O) are dependent upon mass differences with δ 17 O/δ 18 O=0.5, due to the relative mass differences (1 amu vs. 2 amu). Relations that do not follow this are termed mass independent and are the focus of this Minireview. In chemical reactions such as ozone formation, a δ 17 O/δ 18 O=1 is observed. Physical chemical models capture most parameters but differ in basic approach and are reviewed. The mass independent effect is observed in atmospheric species and used to track their chemistry at the modern and ancient Earth, Mars, and the early solar system (meteorites).